Syndrome and acute treatment Fibrinogenopenia - García Valenzuela, Raúl (2015)
29 cases of acute fibrinogenopenia observed in the Department of Obstetrics Hospital of San Francisco de Borja, in a period of eight years (1956- 1963) are studied. The clinical conditions that led to this complication were: a) Premature separation of the placenta (placental abruption and ablatio). b) dystocia and birth injury (adhesions abnormal placenta previa, etc.). c) puerperal septic Pictures (induced abortion, etc.). d) amniotic fluid embolism. The fundamental characteristic of these paintings are prosecuted, both clinically and therapeutically, highlighting the practical value of the "test of clot" to clarify the cause of emergency bleeding.